A postpartum hemorrhage treatment composition and method of making same

CN121177309BActive Publication Date: 2026-09-08NANJING COMTRUE MEDICAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511522178.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2026-09-08
Estimated Expiration
2045-10-23

AI Technical Summary

Technical Problem

首先,传统舌下片剂虽具有一定的崩解性能,但其致密的片剂结构导致药物溶出速度慢,难以在10分钟内达到有效血药浓度

Benefits of technology

[0042]1.快速起效满足急救需求:通过双层微结构设计,面层孔径0.5-5 μm的连通微孔网络配合环糊精纳米域(体积分布中位径80-200 nm)的协同作用,实现崩解时间不大于45秒、舌下给药起效时间不大于10分钟,相比传统口服给药(起效时间15-30分钟)和直肠给药(起效时间10-20分钟),显著缩短止血干预的时间窗口,为产后出血患者争取关键救治时间,特别适用于无法建立静脉通路或转运环节的急救场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121177309B_ABST
    Figure CN121177309B_ABST
Patent Text Reader

Abstract

The application belongs to the field of pharmaceutical preparations, and provides a postpartum hemorrhage treatment composition and a preparation method thereof. The preparation adopts a double-layer microstructure design: a surface layer is a 0.5-5 mu m microporous fast-release layer, a base layer is a dense bearing layer, and the total film thickness is 20-60 mu m. With hydroxypropylmethyl cellulose and 2-hydroxypropyl-beta-cyclodextrin as the matrix, the mass ratio is 80-150:1 and 10-40:1 (relative to misoprostol) respectively, the free water is controlled to be less than or equal to 2.0 wt% through a two-stage drying curve in a low dew point environment, the cyclodextrin nanodomain with a median diameter of 80-200 nm is induced to form, the disintegration time is less than or equal to 45 seconds, the onset time is less than or equal to 10 minutes, and meanwhile, excellent mechanical strength and chemical stability are achieved, so that the contradiction between the rapid release and the structural integrity, the low water content stability and the rapid dissolution, the thickness uniformity and the nanodomain formation of the existing film preparation is solved, and the application has important clinical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pharmaceutical preparations, specifically to a postpartum hemorrhage treatment composition and its preparation method. Background Technology

[0002] Postpartum hemorrhage is the leading cause of maternal mortality worldwide, especially in areas with limited medical resources, where rapid and effective hemostatic intervention is crucial for saving lives. Misoprostol, a prostaglandin analog, exerts its hemostatic effect by promoting uterine contractions and has been recommended by the World Health Organization for the prevention and treatment of postpartum hemorrhage. However, existing routes of administration face numerous limitations in emergency situations: oral administration has a long onset time of 15-30 minutes and is easily affected by gastrointestinal status; intravenous injection requires medical professionals and is difficult to establish intravenous access in transport or remote areas; rectal administration suffers from low patient acceptance and unstable absorption. Therefore, developing a sublingual formulation that can be rapidly administered autonomously in the absence of medical facilities, has a short onset time, and stable absorption is of great significance for reducing postpartum hemorrhage-related mortality and expanding the application of misoprostol in primary healthcare and emergency transport. The sublingual mucosa has a rich blood supply and high permeability. Drug absorption under the tongue can avoid the first-pass effect and enter the bloodstream quickly, providing a physiological basis for achieving onset of action within 10 minutes. However, it places stringent requirements on the rapid disintegration and dissolution properties of the formulation, mucosal adhesion, and stability during transportation.

[0003] Currently, the development of formulations for sublingual administration of misoprostol faces three main technical bottlenecks. First, while traditional sublingual tablets possess some disintegration properties, their dense tablet structure results in slow drug dissolution, making it difficult to achieve effective blood concentrations within 10 minutes. Second, high-porosity film formulations developed to achieve rapid dissolution often suffer from insufficient mechanical strength, making them prone to breakage during production, packaging, and transportation, failing to meet the needs of long-distance delivery and on-site transport. For example, patent CN115252587A discloses an oral fast-dissolving film and its preparation method, but it suffers from high film brittleness and easy breakage during handling. Third, reducing the film's water content is crucial for improving chemical stability and shelf life; however, excessively low water content leads to slow wetting and delayed disintegration in the oral environment. How to maintain rapid wetting and achieve nanoscale drug dispersion to accelerate dissolution under low water content conditions remains a challenge that current technologies have not yet effectively resolved. Furthermore, the industrial production of film formulations faces challenges in controlling the uniformity of thickness and pore structure between and within batches. In particular, when it is necessary to construct specific nanodomains to improve the drug dissolution rate, existing drying processes are difficult to precisely control the phase separation process, resulting in large fluctuations in product quality and limiting the reliability of clinical applications. Summary of the Invention

[0004] The purpose of this invention is to provide a postpartum hemorrhage treatment composition and its preparation method, which solves the problems of coupling contradiction between microporous rapid release structure and anti-fragility transportability in current film formulations, water activity conflict between low water content and high stability and rapid oral wetting and dissolution, and phase behavior conflict between batch-to-batch and intra-batch thickness and mechanical uniformity and the formation of cyclodextrin nanodomains and the requirement for high loading and rapid release.

[0005] This invention employs a dual-layer microstructure synergistic design: the top layer forms a network of interconnected micropores with a pore size of 0.5-5 μm by controlling the phase separation process in the hydroxypropyl methylcellulose matrix, which, together with the nanodomains formed by the self-assembly of 2-hydroxypropyl-β-cyclodextrin, enhances drug dispersion and dissolution, achieving rapid sublingual disintegration and drug release; the base layer provides mechanical support with a dense structure, ensuring the membrane's resistance to brittleness and its transport stability in a dry, low-moisture state; the two layers are integrated through a co-solvent system and precise drying curve control, ensuring both the rapid release function of the top layer and the overall mechanical integrity, achieving a synergistic balance between rapid dissolution and high mechanical strength, low-moisture stability and rapid wetting, and nanodomain functionality and process controllability.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A postpartum hemorrhage treatment composition, which is a sublingual immediate-release therapeutic film, comprises misoprostol; hydroxypropyl methylcellulose; 2-hydroxypropyl-β-cyclodextrin; polyvinylpyrrolidone K30; and a plasticizer selected from glycerin and / or sorbitol; having the following characteristics:

[0008] a) The mass ratio of hydroxypropyl methylcellulose to misoprostol is 80-150:1;

[0009] b) The mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol is 10-40:1;

[0010] c) The mass ratio of polyvinylpyrrolidone K30 to misoprostol is 10-25:1;

[0011] d) The mass ratio of plasticizer to misoprostol is 5-15:1;

[0012] e) The total film thickness is 20-60 μm;

[0013] f) It adopts a double-layer structure, in which the surface layer is a microporous or microfiber structure with a pore size of 0.5-5 μm, and the base layer is a dense load-bearing layer;

[0014] g) The free water content within the membrane is not greater than 2.0 wt%;

[0015] h) The membrane contains nanodomains with a midpoint diameter of 80-200 nm formed by the volume distribution of cyclodextrin.

[0016] Furthermore, the thickness of the surface layer is 5-30 μm.

[0017] Furthermore, the loading of misoprostol in the membrane is 0.3-1.8 wt%.

[0018] Furthermore, the absolute value of the zeta potential of the nanodomain is not less than 15 mV.

[0019] Furthermore, the average molar degree of substitution of the 2-hydroxypropyl-β-cyclodextrin is 0.4-0.8.

[0020] As a concept of this invention, the design of a bilayer microstructured sublingual rapid-release therapeutic membrane is primarily used to enhance the rapid dissolution performance, mechanical stability, and chemical stability of misoprostol. The microporous or microfiber structure of the surface layer is formed by controlling the phase separation behavior of hydroxypropyl methylcellulose in a mixed solvent system. The interconnected channels with a pore size of 0.5-5 μm significantly increase the contact area between the membrane and saliva, shortening the disintegration time to less than 45 seconds. Simultaneously, capillary action within the channels accelerates saliva penetration, promoting rapid drug release. 2-Hydroxypropyl-β-cyclodextrin self-assembles in the membrane matrix to form nanodomains with a median diameter of 80-200 nm in volume distribution. This nanoscale dispersion structure enhances the solubility of misoprostol through inclusion and enables rapid release upon membrane wetting. Combined with the high specific surface area of ​​the surface layer's micropores, this achieves explosive drug dissolution. The base layer employs a dense structure design, primarily composed of a tightly cross-linked network formed by polyvinylpyrrolidone K30 and hydroxypropyl methylcellulose, providing sufficient tensile strength and flexural strength to ensure the film does not crack during production, packaging, and transportation. The addition of plasticizers glycerol and / or sorbitol further improves the flexibility of the base layer, while stabilizing the polymer chain conformation through hydrogen bonding. This invention precisely controls the free water content to no more than 2.0 wt% through two drying curves, ensuring chemical stability and shelf life. Simultaneously, the high hydrophilicity of cyclodextrin in the nanodomains compensates for the low water content of the film, allowing it to rapidly absorb water and disintegrate under the tongue. This bilayer synergistic design achieves a balance between rapid dissolution and mechanical strength, and between low water content stability and rapid wetting, meeting the dual requirements of rapid onset of action and formulation reliability in postpartum hemorrhage emergency scenarios.

[0021] This invention also discloses a method for preparing a postpartum hemorrhage treatment composition, characterized by comprising the following steps:

[0022] S1. Hydroxypropyl methylcellulose, 2-hydroxypropyl-β-cyclodextrin and polyvinylpyrrolidone K30 are dispersed and dissolved in a mixed solvent of water and ethanol, with an ethanol volume fraction of 40-90 vol%. After shearing and dispersing at 8000-12000 rpm for 5-8 min, misoprostol and plasticizer are added and degassing is performed.

[0023] S2. Apply the film with a wet film thickness of 120-200 μm by blade coating, and dry it according to a two-stage drying curve of 30 ℃ for 8-12 min followed by 25 ℃ for 10-15 min until the free water content in the film is no more than 2.0 wt%.

[0024] S3. Cut into single sheets to obtain sublingual immediate-release therapeutic films with a total film thickness of 20-60 μm, and complete the sealing and packaging.

[0025] Furthermore, the degassing is carried out under a vacuum of -0.09 to -0.095 MPa for 10-20 min.

[0026] Furthermore, the dew point of the dry environment of S2 is not higher than -10 ℃.

[0027] Furthermore, the pore size of the surface layer is obtained through phase separation induction, and the pore size is 0.5-5 μm.

[0028] As another aspect of this invention, the preparation method combining a mixed solvent system and two drying curves is primarily used to precisely construct bilayer microstructures and control the formation of nanodomains. In step S1, a mixed solvent of water and ethanol is used, with an ethanol volume fraction of 40-90 vol%. The difference in solubility of hydroxypropyl methylcellulose in different solvents induces phase separation: the high ethanol content promotes local aggregation of polymer chains, laying the foundation for micropore formation during subsequent drying. Simultaneously, 2-hydroxypropyl-β-cyclodextrin maintains good dispersion in this solvent system, forming a precursor structure for inclusion complexes with misoprostol. High-speed shear dispersion at 8000-12000 rpm ensures uniform distribution of components at the nano to micrometer scale, creating conditions for the self-assembly of nanodomains. Vacuum degassing is performed at -0.09 to -0.095 MPa for 10-20 minutes, effectively removing air bubbles from the solution and preventing the formation of large pores inside the membrane that could affect mechanical properties. The two drying curves in step S2 are crucial for constructing the bilayer structure: In the first stage, the temperature is maintained at 30°C for 8-12 minutes, controlling the solvent evaporation rate to allow for sufficient phase separation in the surface region, forming a connected microporous network. Simultaneously, cyclodextrin molecules self-assemble into nanodomains driven by the solvent concentration gradient. In the second stage, the temperature is lowered to 25°C and maintained for 10-15 minutes to slow the drying rate and prevent excessively rapid curing of the film surface, which could lead to internal stress accumulation and increased brittleness, ensuring a dense and uniform structure in the base layer. The drying environment's dew point is kept below -10°C, and environmental humidity is strictly controlled to prevent external moisture infiltration from affecting the precise control of free water content, ultimately achieving a low-moisture stable state with no more than 2.0 wt% free water. The cutting tolerance of ±0.2 mm in step S3 ensures the uniformity of each tablet's weight. The aluminum-aluminum cold-formed blister packaging provides excellent moisture and oxygen barrier properties, ensuring product stability during storage and transportation. The entire preparation process, through precise control of solvent composition, shear parameters, and drying curves, achieves reproducible preparation of three key features: bilayer structure, nanoscale domain, and low water content.

[0029] The present invention also discloses the use of a postpartum hemorrhage treatment composition in the preparation of a medicament for treating postpartum hemorrhage, wherein the composition is administered sublingually to achieve an onset time of no more than 10 minutes.

[0030] Furthermore, the thickness ratio of the surface layer to the base layer is 0.4-1.5.

[0031] Furthermore, the disintegration time of the composition is no more than 45 s.

[0032] Furthermore, the composition further comprises sucralose in an amount of 0.02-0.20 wt%.

[0033] Furthermore, the composition further comprises citric acid in a content of 0.05-0.50 wt%, and sodium citrate dihydrate in a content of 0.05-0.50 wt%.

[0034] Furthermore, the volume fraction of ethanol in S1 is 50-80 vol.

[0035] Furthermore, the cutting tolerance is ±0.2 mm.

[0036] Furthermore, the packaging is an aluminum-aluminum cold-formed blister pack.

[0037] Furthermore, the mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol is 15-30:1.

[0038] Furthermore, the plasticizer is a combination of glycerol and sorbitol, with a mass ratio of 1-3:1-3.

[0039] Furthermore, the application is intended for sublingual administration in scenarios where intravenous access or transport cannot be established, so as to achieve an onset time of no more than 10 minutes.

[0040] Hydroxypropyl methylcellulose and 2-hydroxypropyl-β-cyclodextrin each play key roles and exhibit significant synergistic effects in the sublingual immediate-release therapeutic membrane of this invention. Hydroxypropyl methylcellulose, as the main film-forming matrix, provides the mechanical framework of the membrane through its long-chain polymer structure. It forms a three-dimensional network through intermolecular hydrogen bonds and physical entanglement, endowing the membrane with basic tensile strength and flexibility. Simultaneously, the phase separation behavior of hydroxypropyl methylcellulose in mixed solvent systems is the basis for constructing the surface microporous structure, focusing on providing mechanical support and inducing pore formation. 2-hydroxypropyl-β-cyclodextrin focuses on improving the solubility of misoprostol and constructing a nanoscale drug reservoir. Its cyclic molecular structure, characterized by hydrophobic interior and hydrophilic exterior, allows it to encapsulate misoprostol molecules. Through hydrophobic interactions, the drug is encapsulated within the cyclodextrin cavity, significantly improving the apparent solubility of the drug in an aqueous environment. Simultaneously, the hydrogen bonding between cyclodextrin molecules drives its self-assembly into nanodomains with a median diameter of 80-200 nm, forming a high-density drug dispersion region. In terms of improving rapid dissolution performance, hydroxypropyl methylcellulose increases the membrane's specific surface area and salivary permeation rate by forming micropores, providing a physical channel for rapid drug release. Meanwhile, 2-hydroxypropyl-β-cyclodextrin accelerates drug dissolution at the molecular level through inclusion complexation and nanodomain structures. The synergistic effect of both reduces disintegration time to less than 45 seconds and accelerates drug release. Regarding mechanical stability, hydroxypropyl methylcellulose provides the main structural strength, while the nanodomains of 2-hydroxypropyl-β-cyclodextrin act as a reinforcing phase distributed within the matrix, further enhancing matrix density and resistance to brittleness through hydrogen bonding with polymer chains. More importantly, the high hydrophilicity of the cyclodextrin nanodomains compensates for the insufficient wettability of the low-water-content membrane (free water ≤ 2.0 wt%), allowing the membrane to rapidly absorb water and disintegrate under the tongue. Simultaneously, the low water content of hydroxypropyl methylcellulose ensures chemical stability. The synergistic effect of both achieves a balance between low-water-content stability and rapid wetting and dissolution, far exceeding the simple summation of individual components.

[0041] (3) Beneficial technical effects

[0042] 1. Rapid onset of action to meet emergency needs: Through a double-layer microstructure design, the interconnected microporous network with a surface pore size of 0.5-5 μm, combined with the synergistic effect of cyclodextrin nanodomains (median diameter of volume distribution 80-200 nm), achieves a disintegration time of no more than 45 seconds and an onset of action of no more than 10 minutes for sublingual administration. Compared with traditional oral administration (onset of action 15-30 minutes) and rectal administration (onset of action 10-20 minutes), it significantly shortens the time window for hemostasis intervention, buying critical treatment time for postpartum hemorrhage patients. It is especially suitable for emergency scenarios where intravenous access or transportation cannot be established.

[0043] 2. Mechanical stability ensures reliable handling: The dense load-bearing structure of the substrate combined with the plasticizer-optimized flexibility design enables the ultra-thin film sheet with a total thickness of 20-60 μm to maintain excellent tensile strength and bending resistance in a dry state (free water ≤2.0 wt%). This avoids the problem of easy cracking of traditional high-porosity instant films during packaging, transportation and field handling, ensuring the integrity and usability of the product when it is delivered to primary healthcare institutions or carried by individuals, and improving the reliability of the formulation in practical applications.

[0044] 3. Extended shelf life due to improved chemical stability: By precisely controlling free water content to no more than 2.0 wt% through two drying curves (30℃ 8-12 min → 25℃ 10-15 min), the risk of moisture-induced hydrolytic degradation of misoprostol is significantly reduced. At the same time, the aluminum-aluminum cold-formed blister packaging provides excellent moisture and oxygen barrier protection, ensuring that the product has a long shelf life and stable drug content under normal temperature storage conditions, reducing cold chain transportation and storage costs, and facilitating its promotion and application in areas with limited medical resources.

[0045] 4. Enhanced drug dissolution through nanodomains: The nanodomains formed by the self-assembly of 2-hydroxypropyl-β-cyclodextrin (with an absolute zeta potential value ≥15 mV, indicating good dispersion stability) disperse misoprostol to the nanoscale through inclusion, significantly improving the drug's dissolution rate and bioavailability in the sublingual mucosa environment. Combined with the capillary action and high specific surface area of ​​the surface micropores, this achieves explosive drug release, ensuring rapid attainment of effective blood drug concentrations and enhancing therapeutic efficacy.

[0046] 5. Process controllability ensures batch consistency: By employing a mixed solvent system (water + ethanol, ethanol 40-90 vol%), high-speed shear dispersion (8000-12000 rpm), precise drying curves, and a low dew point environment (dew point ≤ -10℃), strict control of process parameters achieves high batch-to-batch and intra-batch consistency in key quality attributes such as bilayer structure, nanoscale size, total film thickness, and free water content. A cutting tolerance of ±0.2 mm further ensures dosage uniformity, meeting the stringent quality requirements of industrial production and clinical applications. Attached Figure Description

[0047] Figure 1 This invention relates to the effect of the mass ratio of hydroxypropyl methylcellulose to misoprostol on disintegration time and tensile strength.

[0048] Figure 2 This invention investigates the effect of the mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol on the median diameter of the nanodomain and the dissolution rate at 15 minutes.

[0049] Figure 3 This invention illustrates the effect of total film thickness on disintegration time and tensile strength.

[0050] Figure 4 This invention relates to the effect of ethanol volume fraction on the midpoint diameter and free water content of the nanodomain.

[0051] Figure 5 The XPS spectrum of the sublingual immediate-release therapeutic film of Example 1 of the present invention is shown.

[0052] Figure 6 This is a C1s high-resolution XPS image of the sublingual immediate-release therapeutic membrane of Example 1 of the present invention.

[0053] Figure 7 This is the O 1s high-resolution XPS spectrum of the sublingual rapid-release therapeutic membrane of Example 1 of the present invention.

[0054] Figure 8 This is the N 1s high-resolution XPS spectrum of the sublingual rapid-release therapeutic membrane of Example 1 of the present invention.

[0055] Figure 9 This is a high-resolution XPS image of Cl 2p of the sublingual immediate-release therapeutic membrane of Example 1 of the present invention.

[0056] Figure 10 This is a high-resolution XPS image of Na 1s from the sublingual rapid-release therapeutic membrane of Example 1 of the present invention.

[0057] Figure 11 This is a cross-sectional topography diagram of the surface layer in Embodiment 1 of the present invention.

[0058] Figure 12 This is a top view of the surface layer in Embodiment 1 of the present invention. Detailed Implementation

[0059] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0060] Example 1

[0061] I. Composition of the Composition

[0062] The postpartum hemorrhage treatment composition of this embodiment is a sublingual immediate-release therapeutic film, comprising the following components:

[0063] 1. Active ingredient: Misoprostol (chemically pure, purity ≥99.0%, commercially available), loading amount 0.8 wt.

[0064] 2. Film-forming material: Hydroxypropyl methylcellulose (HPMC E5, viscosity 4-6 mPa·s, pharmaceutical grade, commercially available): mass ratio of hydroxypropyl methylcellulose to misoprostol is 100:1;

[0065] Polyvinylpyrrolidone K30 (K value 29-32, pharmaceutical grade, commercially available): mass ratio of misoprostol to 15:1.

[0066] 3. Inclusion material: 2-hydroxypropyl-β-cyclodextrin (average molar degree of substitution 0.6, pharmaceutical grade, commercially available): mass ratio of 20:1 to misoprostol.

[0067] 4. Plasticizer: Glycerin (analytical grade, purity ≥99.5%, commercially available) and sorbitol (analytical grade, purity ≥99.0%, commercially available) are compounded in a mass ratio of 2:2, and the total amount used is in a mass ratio of 8:1 with misoprostol.

[0068] 5. Flavoring agent: Sucralose (purity ≥98%, food grade, commercially available): 0.10 wt.

[0069] 6. pH adjuster: Citric acid (anhydrous, analytical grade, commercially available): 0.20 wt%

[0070] Sodium citrate dihydrate (analytical grade, commercially available): 0.20 wt%.

[0071] 7. Solvent: A mixture of purified water and anhydrous ethanol (analytical grade, commercially available), with an ethanol volume fraction of 60 vol.

[0072] II. Preparation Method

[0073] Step 1: Preparation of film-forming solution

[0074] Hydroxypropyl methylcellulose, 2-hydroxypropyl-β-cyclodextrin, and polyvinylpyrrolidone K30 were dispersed in a mixed solvent of purified water and anhydrous ethanol (ethanol volume fraction 60 vol%), and stirred at room temperature for 1 hour until completely dissolved. The solution was then sheared and dispersed for 6 minutes using a high-shear disperser (10000 rpm) to ensure homogeneity. Misoprostol, glycerol, sorbitol, sucralose, citric acid, and sodium citrate dihydrate were added, and stirring continued for 30 minutes until completely dissolved. The film-forming solution was placed in a vacuum degassing chamber at a vacuum degree of -0.092 MPa for 15 minutes to remove air bubbles.

[0075] Step 2: Apply coating to form a film

[0076] The degassed film-forming solution was poured into the feed trough of the doctor blade coater. A doctor blade coater was used, with the wet film thickness set to 150 μm, to coat the polyester film substrate. The coating speed was 1.5 m / min, and the coating pressure was controlled at 0.05 MPa.

[0077] Step 3: Two-stage drying

[0078] The wet film applied immediately enters the drying tunnel (drying environment: dew point -12℃, relative humidity <10%):

[0079] First drying stage: Temperature 30℃, maintain for 10 minutes (partial solvent evaporation, induced phase separation to form a microporous surface layer).

[0080] Second stage of drying: Temperature 25℃, maintain for 12 minutes (continue drying until free water ≤ 2.0 wt%)

[0081] The drying process utilizes a slight negative pressure (-50 Pa) to assist solvent evaporation.

[0082] Step 4: Cutting and Packaging

[0083] The dried film is peeled off from the substrate and cut into 2.5 cm × 2.5 cm single sheets (cutting tolerance ±0.2 mm) using a precision cutting machine. Each sheet contains 200 μg of misoprostol. The single sheets are placed in aluminum-aluminum cold-formed blister packaging, sealed with nitrogen, and stored at 2-8°C.

[0084] III. Product Features

[0085] 1. Membrane structure characteristics: Total membrane thickness: 35 μm

[0086] Dual-layer structure: The surface layer is a microporous structure (pore size 1.5 μm) with a thickness of 12 μm; the base layer is a dense load-bearing layer with a thickness of 23 μm; the thickness ratio of the surface layer to the base layer is 0.52.

[0087] 2. Physicochemical characteristics: Free water content: 1.5 wt% (Kal Fischer method); Median diameter of nanodomain volume distribution: 120 nm (dynamic light scattering method); Absolute value of zeta potential: 18 mV (Zeta potentiometer); Disintegration time: 35 s (in artificial saliva, 37℃).

[0088] 3. Pharmaceutical characteristics: Misoprostol loading: 0.8 wt%; content uniformity: 95.0-105.0% (HPLC determination of 10 tablets).

[0089] IV. Features of the Implementation Examples

[0090] This embodiment employs a moderate parameter design with appropriate proportions of each component in the formulation. The 60 vol% ethanol content of the film-forming solution facilitates the dissolution and dispersion of hydroxypropyl methylcellulose and cyclodextrin. In the two-stage drying process, the first stage at 30°C induces rapid solvent evaporation, forming a microporous surface layer, while the second stage at 25°C avoids high-temperature degradation of misoprostol. The 35 μm film thickness balances mechanical strength and rapid disintegration. The microporous structure of the surface layer (1.5 μm pore size) increases the specific surface area, promoting saliva penetration. The nanodomains (120 nm) formed by the self-assembly of cyclodextrin enhance the dissolution rate of misoprostol. Sucralose is added to the formulation to improve palatability, and a citrate / sodium citrate buffer system (pH approximately 5.0-5.5) improves the suitability for sublingual administration. This embodiment is suitable for routine postpartum hemorrhage prevention and treatment scenarios, allowing sublingual administration without intravenous access, with an estimated onset time of 6-8 minutes.

[0091] Example 2

[0092] I. Composition of the Composition

[0093] The postpartum hemorrhage treatment composition of this embodiment is a sublingual immediate-release therapeutic film, comprising the following components:

[0094] 1. Active ingredient: Misoprostol (chemically pure, purity ≥99.0%, commercially available), loading 1.5 wt.

[0095] 2. Film-forming materials:

[0096] Hydroxypropyl methylcellulose (HPMC E5, viscosity 4-6 mPa·s, pharmaceutical grade, commercially available): mass ratio of 85:1 with misoprostol.

[0097] Polyvinylpyrrolidone K30 (K value 29-32, pharmaceutical grade, commercially available): mass ratio of misoprostol to 12:1.

[0098] 3. Packaging materials:

[0099] 2-Hydroxypropyl-β-cyclodextrin (average molar degree of substitution 0.7, pharmaceutical grade, commercially available): mass ratio of misoprostol 35:1.

[0100] 4. Plasticizers:

[0101] Glycerin (analytical grade, purity ≥99.5%, commercially available) and sorbitol (analytical grade, purity ≥99.0%, commercially available) were combined in a mass ratio of 3:1, and the total amount used was in a mass ratio of 6:1 to misoprostol.

[0102] 5. Flavoring agents:

[0103] Sucralose (purity ≥98%, food grade, commercially available): 0.15 wt.

[0104] 6. pH adjuster:

[0105] Citric acid (anhydrous, analytical grade, commercially available): 0.30 wt%

[0106] Sodium citrate dihydrate (analytical grade, commercially available): 0.30 wt.

[0107] 7. Solvent: A mixture of purified water and anhydrous ethanol (analytical grade, commercially available), with an ethanol volume fraction of 75 vol%.

[0108] II. Preparation Method

[0109] Step 1: Preparation of film-forming solution

[0110] Hydroxypropyl methylcellulose, 2-hydroxypropyl-β-cyclodextrin, and polyvinylpyrrolidone K30 were dispersed in a mixed solvent of purified water and anhydrous ethanol (75 vol%), and stirred at room temperature for 1.5 hours until completely dissolved. The solution was then sheared and dispersed for 7 minutes using a high-shear disperser (11000 rpm) to homogenize the solution and promote nanodomain formation. Misoprostol, glycerol (75% of the total plasticizer), sorbitol (25% of the total plasticizer), sucralose, citric acid, and sodium citrate dihydrate were added, and stirring continued for 40 minutes until completely dissolved. The film-forming solution was placed in a vacuum degassing chamber at -0.094 MPa for 18 minutes to thoroughly remove air bubbles.

[0111] Step 2: Apply coating to form a film

[0112] The degassed film-forming solution was poured into the feed trough of the doctor blade coater. A doctor blade coater was used, with the wet film thickness set to 130 μm, to coat the polyester film substrate. The coating speed was 2.0 m / min, and the coating pressure was controlled at 0.04 MPa.

[0113] Step 3: Two-stage drying

[0114] The wet film after coating immediately enters the drying channel (drying environment dew point -15℃, relative humidity <8%): First stage drying: temperature 30℃, hold for 9 minutes (ethanol evaporates rapidly, inducing phase separation to form a microporous surface layer with small pores); Second stage drying: temperature 25℃, hold for 11 minutes (continue drying until free water ≤2.0 wt%). The drying process uses micro negative pressure (-80 Pa) to accelerate solvent evaporation.

[0115] Step 4: Cutting and Packaging

[0116] The dried film is peeled off from the substrate and cut into 2.0 cm × 2.0 cm single sheets (cutting tolerance ±0.2 mm) using a precision cutting machine. Each sheet contains 200 μg of misoprostol. The single sheets are placed in aluminum-aluminum cold-formed blister packaging, sealed with nitrogen, and stored at 2-8°C.

[0117] III. Product Features

[0118] Membrane structure characteristics:

[0119] Total film thickness: 22 μm;

[0120] Dual-layer structure: The surface layer is a microporous structure (pore size 0.8 μm) with a thickness of 8 μm; the base layer is a dense load-bearing layer with a thickness of 14 μm;

[0121] Top layer to base layer thickness ratio: 0.57.

[0122] Physicochemical characteristics:

[0123] Free water content: 1.2 wt% (determined by Karl Fischer method);

[0124] Median diameter of the nanodomain volume distribution: 180 nm (determined by dynamic light scattering method);

[0125] absolute value of zeta potential: 22 mV (measured by a zeta potential meter);

[0126] Disintegration time: 28 s (in artificial saliva, 37°C).

[0127] Pharmaceutical characteristics:

[0128] Misoprostol loading: 1.5 wt%;

[0129] Content uniformity: 95.0-105.0% (HPLC determination of 10 tablets).

[0130] IV. Features of the Implementation Examples

[0131] This embodiment features an optimized design for rapid onset of action. A high misoprostol loading (1.5 wt%) provides sufficient dosage, while a high ratio of 2-hydroxypropyl-β-cyclodextrin (35:1) forms more nanodomains (180 nm) to enhance drug dissolution. A high-ethanol content film-forming solution (75 vol%) rapidly evaporates, inducing the formation of a small-pore microporous surface layer (0.8 μm), significantly increasing the specific surface area. The thin film design (total film thickness 22 μm) reduces diffusion distance, and the surface layer thickness of 8 μm, close to the lower limit, ensures rapid saliva penetration, shortening the disintegration time to 28 seconds. A high shear dispersion strength (11000 rpm, 7 minutes) promotes nanodomain formation and increases the zeta potential (22 mV), improving nanodomain stability. A glycerol-based plasticizer ratio (3:1) maintains film flexibility while reducing moisture absorption. This embodiment is suitable for emergency postpartum hemorrhage scenarios requiring rapid onset of action, such as home delivery, during transport, or in primary healthcare facilities without intravenous access. The expected onset time is 4-6 minutes.

[0132] Example 3

[0133] The postpartum hemorrhage treatment composition of this embodiment is a sublingual immediate-release therapeutic film, comprising the following components:

[0134] Active ingredient: Misoprostol (chemically pure, purity ≥99.0%, commercially available), loading 0.5 wt%.

[0135] Film-forming materials:

[0136] Hydroxypropyl methylcellulose (HPMC E5, viscosity 4-6 mPa·s, pharmaceutical grade, commercially available): mass ratio of 140:1 to misoprostol;

[0137] Polyvinylpyrrolidone K30 (K value 29-32, pharmaceutical grade, commercially available): mass ratio of misoprostol to 22:1;

[0138] Packaging materials:

[0139] 2-Hydroxypropyl-β-cyclodextrin (average molar degree of substitution 0.5, pharmaceutical grade, commercially available): mass ratio of 15:1 to misoprostol.

[0140] Plasticizer:

[0141] Glycerin (analytical grade, purity ≥99.5%, commercially available) and sorbitol (analytical grade, purity ≥99.0%, commercially available) were mixed in a mass ratio of 1:3, and the total amount used was in a mass ratio of 12:1 to misoprostol.

[0142] Flavoring agent:

[0143] Sucralose (purity ≥98%, food grade, commercially available): 0.05 wt%.

[0144] pH adjuster:

[0145] Citric acid (anhydrous, analytical grade, commercially available): 0.10 wt%

[0146] Sodium citrate dihydrate (analytical grade, commercially available): 0.10 wt%

[0147] Solvent: A mixture of purified water and anhydrous ethanol (analytical grade, commercially available), with an ethanol volume fraction of 50 vol.

[0148] II. Preparation Method

[0149] Step 1: Preparation of film-forming solution

[0150] Hydroxypropyl methylcellulose, 2-hydroxypropyl-β-cyclodextrin, and polyvinylpyrrolidone K30 were dispersed in a mixed solvent of purified water and anhydrous ethanol (ethanol volume fraction 50 vol%), and stirred at room temperature for 2 hours until completely dissolved. The solution was then sheared and dispersed for 5.5 minutes using a high-shear disperser (9000 rpm) to ensure homogeneity. Misoprostol, glycerol (25% of the total plasticizer), sorbitol (75% of the total plasticizer), sucralose, citric acid, and sodium citrate dihydrate were added, and stirring continued for 25 minutes until completely dissolved. The film-forming solution was placed in a vacuum degassing chamber at a vacuum degree of -0.090 MPa for 12 minutes to remove air bubbles.

[0151] Step 2: Apply coating to form a film

[0152] The degassed film-forming solution was poured into the feed trough of the doctor blade coater. A doctor blade coater was used, with the wet film thickness set to 190 μm, to coat the polyester film substrate. The coating speed was 1.0 m / min, and the coating pressure was controlled at 0.06 MPa.

[0153] Step 3: Two-stage drying

[0154] The wet film applied immediately enters the drying tunnel (drying environment: dew point -10℃, relative humidity <12%).

[0155] First drying stage: Temperature 30℃, maintain for 11 minutes (slow solvent evaporation, forming a microporous surface layer with larger pore size).

[0156] Second drying stage: Temperature 25℃, maintain for 14 minutes (dry thoroughly until free water ≤ 2.0 wt%)

[0157] The drying process employs a slight negative pressure (-30 Pa) to gently assist solvent evaporation.

[0158] Step 4: Cutting and Packaging

[0159] The dried film is peeled off from the substrate and cut into 3.5 cm × 3.5 cm single sheets (cutting tolerance ±0.2 mm) using a precision cutting machine. Each sheet contains 200 μg of misoprostol. The single sheets are placed in aluminum-aluminum cold-formed blister packaging, sealed with nitrogen, and stored at 2-8°C.

[0160] III. Product Features

[0161] Membrane structure characteristics:

[0162] Total film thickness: 55 μm;

[0163] Dual-layer structure: The surface layer is a microporous structure (pore size 3.5 μm) with a thickness of 22 μm; the base layer is a dense load-bearing layer with a thickness of 33 μm;

[0164] Top layer to base layer thickness ratio: 0.67.

[0165] Physicochemical characteristics:

[0166] Free water content: 1.8 wt% (determined by Karl Fischer method);

[0167] Median diameter of the nanodomain volume distribution: 95 nm (determined by dynamic light scattering method);

[0168] absolute value of zeta potential: 16 mV (measured by a Zeta potential meter);

[0169] Disintegration time: 42 s (in artificial saliva, 37°C).

[0170] Pharmaceutical characteristics:

[0171] Misoprostol loading: 0.5 wt%

[0172] Content uniformity: 95.0-105.0% (HPLC determination of 10 tablets).

[0173] IV. Features of the Implementation Examples

[0174] This embodiment features an optimized design to improve product stability and mechanical strength. A higher hydroxypropyl methylcellulose ratio (140:1) and a polyvinylpyrrolidone K30 ratio (22:1) enhance film-forming properties and film strength. A thicker film design (total film thickness 55 μm, close to the upper limit of 60 μm) provides ample mechanical protection, reducing the risk of breakage during transportation and storage. A 22 μm topcoat thickness increases protection, and a larger pore size (3.5 μm) slows disintegration while still meeting the 45-second standard. A medium ethanol content film-forming solution (50 vol%) balances solubility and drying rate, and a longer two-stage drying time (11+14 minutes) ensures adequate control of free water (1.8 wt%, close to the upper limit, 2.0 wt%, but acceptable), improving storage stability. A sorbitol-based plasticizer ratio (1:3) provides better water retention and anti-crystallization properties. A lower misoprostol loading (0.5 wt%) reduces the risk of drug aggregation and improves content uniformity. This embodiment is applicable to scenarios requiring long-term storage or harsh transportation conditions (such as drug reserves in tropical or remote areas). Although the disintegration time of 42 seconds is slightly long, it is still within the range of rapid onset of action, and the expected onset time is 8-10 minutes.

[0175] Example 4

[0176] I. Composition of the Composition

[0177] The postpartum hemorrhage treatment composition of this embodiment is a sublingual immediate-release therapeutic film, comprising the following components:

[0178] Active ingredient: Misoprostol (chemically pure, purity ≥99.0%, commercially available), loading 0.3 wt%;

[0179] Film-forming materials:

[0180] Hydroxypropyl methylcellulose (HPMC E5, viscosity 4-6 mPa·s, pharmaceutical grade, commercially available): mass ratio of 150:1 with misoprostol;

[0181] Polyvinylpyrrolidone K30 (K value 29-32, pharmaceutical grade, commercially available): mass ratio of misoprostol to 10:1;

[0182] Packaging materials:

[0183] 2-Hydroxypropyl-β-cyclodextrin (average molar degree of substitution 0.4, pharmaceutical grade, commercially available): mass ratio of 40:1 to misoprostol.

[0184] Plasticizer:

[0185] Glycerin (analytical grade, purity ≥99.5%, commercially available) and sorbitol (analytical grade, purity ≥99.0%, commercially available) were mixed in a mass ratio of 1:1, and the total amount used was in a mass ratio of 5:1 to misoprostol.

[0186] Flavoring agent:

[0187] Sucralose (purity ≥98%, food grade, commercially available): 0.02 wt%

[0188] pH adjuster:

[0189] Citric acid (anhydrous, analytical grade, commercially available): 0.05 wt%

[0190] Sodium citrate dihydrate (analytical grade, commercially available): 0.50 wt%

[0191] Solvent: A mixture of purified water and anhydrous ethanol (analytical grade, commercially available), with an ethanol volume fraction of 40 vol%.

[0192] II. Preparation Method

[0193] Step 1: Preparation of film-forming solution

[0194] Hydroxypropyl methylcellulose, 2-hydroxypropyl-β-cyclodextrin, and polyvinylpyrrolidone K30 were dispersed in a mixed solvent of purified water and anhydrous ethanol (ethanol volume fraction 40 vol%), and stirred at room temperature for 2.5 hours until completely dissolved. The solution was then sheared and dispersed for 8 minutes using a high-shear disperser (8000 rpm) to ensure homogeneity. Misoprostol, glycerol, sorbitol (1:1 by mass), sucralose, citric acid, and sodium citrate dihydrate were added, and stirring continued for 35 minutes until completely dissolved. The film-forming solution was placed in a vacuum degassing chamber at a vacuum degree of -0.095 MPa for 20 minutes to thoroughly remove air bubbles.

[0195] Step 2: Apply coating to form a film

[0196] The degassed film-forming solution was poured into the feed trough of the doctor blade coater. A doctor blade coater was used, with the wet film thickness set to 120 μm, to coat the polyester film substrate. The coating speed was 1.2 m / min, and the coating pressure was controlled at 0.05 MPa.

[0197] Step 3: Two-stage drying

[0198] The wet film applied immediately enters the drying tunnel (drying environment: dew point -10℃, relative humidity <12%).

[0199] First drying stage: Temperature 30℃, maintain for 8 minutes (slow phase separation induced under low ethanol content);

[0200] Second stage of drying: Temperature 25℃, maintain for 15 minutes (extend drying to ensure free water ≤2.0 wt%).

[0201] The drying process uses a slight negative pressure (-40 Pa) to assist solvent evaporation.

[0202] Step 4: Cutting and Packaging

[0203] The dried film is peeled off from the substrate and cut into 4.0 cm × 4.0 cm single sheets (cutting tolerance ±0.2 mm) using a precision cutting machine. Each sheet contains 200 μg of misoprostol. The single sheets are placed in aluminum-aluminum cold-formed blister packaging, sealed with nitrogen, and stored at 2-8°C.

[0204] III. Product Features

[0205] Membrane structure characteristics:

[0206] Total film thickness: 20 μm.

[0207] The structure consists of two layers: the surface layer is a microfiber structure (fiber diameter 0.5 μm) with a thickness of 5 μm; the base layer is a dense load-bearing layer with a thickness of 15 μm.

[0208] Top layer to base layer thickness ratio: 0.33.

[0209] Physicochemical characteristics:

[0210] Free water content: 1.9 wt% (determined by Karl Fischer method);

[0211] Median diameter of nanodomain volume distribution: 85 nm (determined by dynamic light scattering method);

[0212] absolute value of zeta potential: 15 mV (measured by a Zeta potential meter);

[0213] Disintegration time: 32 s (in artificial saliva, 37°C);

[0214] Pharmaceutical characteristics:

[0215] Misoprostol loading: 0.3 wt%;

[0216] Content uniformity: 95.0-105.0% (HPLC determination of 10 tablets).

[0217] This embodiment uses a combination of specific parameters for system verification: hydroxypropyl methylcellulose ratio 150:1, polyvinylpyrrolidone K30 ratio 10:1, 2-hydroxypropyl-β-cyclodextrin ratio 40:1 with a molar substitution degree of 0.4, plasticizer ratio 5:1, total film thickness 20 μm, surface layer thickness 5 μm, surface layer pore size 0.5 μm to form a microfiber structure, median diameter of the nanodomain 85 nm, absolute value of zeta potential 15 mV, sucralose content 0.02 wt%, citric acid content 0.05 wt%, sodium citrate content 0.50 wt% to form a relatively strong alkaline buffer, ethanol volume fraction 40 vol%, wet film thickness 120 μm, degassing vacuum degree -0.095 MPa, degassing time 20 minutes, shearing time 8 minutes, first stage drying time 8 minutes, second stage drying time 15 minutes. A qualified product is obtained through precise process control: While the 40 vol% ethanol film-forming solution has a relatively slow dissolution rate, extended stirring and shearing times ensure uniform dispersion. The 20 μm film design utilizes a high ratio of 150:1 hydroxypropyl methylcellulose and sufficient drying time to ensure film integrity. A 5:1 plasticizer ratio, achieved through the equal-ratio blending of glycerol and sorbitol, improves flexibility. A 40:1 cyclodextrin ratio, achieved through a 0.4 molar substitution degree and sufficient shearing dispersion, forms stable nanodomains (85 nm, zeta potential of 15 mV, meeting stability requirements). The addition of 0.02 wt% sucralose and 0.05 wt% citric acid, compensated by 0.50 wt% sodium citrate, provides alkaline buffering and masks bitterness. This embodiment is suitable for cost-sensitive or special patient populations (such as those sensitive to sweeteners), with an expected onset time of 7-9 minutes.

[0218] Comparative Example 1

[0219] The preparation method is basically the same as in Example 1, except that the mass ratio of hydroxypropyl methylcellulose to misoprostol is 70:1, while the amounts of other components and preparation conditions remain unchanged.

[0220] Comparative Example 2

[0221] The preparation method is basically the same as in Example 1, except that the mass ratio of hydroxypropyl methylcellulose to misoprostol is 160:1, while the amounts of other components and preparation conditions remain unchanged.

[0222] Comparative Example 3

[0223] It is basically the same as Example 1, except that the mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol is 8:1, and the amounts of other components and preparation conditions remain unchanged.

[0224] Comparative Example 4

[0225] The preparation method is basically the same as in Example 1, except that the mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol is 45:1, while the amounts of other components and preparation conditions remain unchanged.

[0226] Comparative Example 5

[0227] The preparation method is basically the same as in Example 1, except that the mass ratio of polyvinylpyrrolidone K30 to misoprostol is 8:1, while the amounts of other components and preparation conditions remain unchanged.

[0228] Comparative Example 6

[0229] It is basically the same as Example 1, except that the mass ratio of plasticizer to misoprostol is 3:1, and the amounts of other components and preparation conditions remain unchanged.

[0230] Comparative Example 7

[0231] It is basically the same as Example 1, except that the total film thickness is 15 μm, which is achieved by reducing the wet film thickness to 110 μm, while the amount of other components and preparation conditions remain unchanged.

[0232] Comparative Example 8

[0233] It is basically the same as Example 1, except that the total film thickness is 70 μm, which is achieved by increasing the wet film thickness to 210 μm, while the amount of other components and preparation conditions remain unchanged.

[0234] Comparative Example 9

[0235] The process is basically the same as in Example 1, except that a single-layer structure is used (without a double-layer design). The film-forming liquid is directly applied and then dried uniformly (30°C for 10 minutes and 25°C for 12 minutes). No layered structure of microporous surface layer and dense substrate layer is formed. The amounts of other components remain unchanged.

[0236] Comparative Example 10

[0237] The process is basically the same as in Example 1, except that the temperature of the first stage of the two-stage drying is 45°C and maintained for 10 minutes, while the drying conditions of the second stage remain unchanged, and the amounts of other components and preparation conditions remain unchanged.

[0238] Comparative Example 11

[0239] The process is basically the same as in Example 1, except that the film-forming solution does not undergo a high-shear dispersion step. Instead, it is stirred with ordinary magnetic stirring at 300 rpm for 2 hours until it is uniformly dissolved. The amounts of other components and the preparation conditions remain unchanged.

[0240] Comparative Example 12

[0241] It is basically the same as Example 1, except that the volume fraction of ethanol is 30 vol%, and the amounts of other components and preparation conditions remain unchanged.

[0242] Comparative Example 13

[0243] It is basically the same as Example 1, except that the volume fraction of ethanol is 95 vol%, and the amounts of other components and preparation conditions remain unchanged.

[0244] Performance testing:

[0245] Experiment 1 Disintegration Time Limit Test

[0246] Test Subject: Sublingual immediate-release therapeutic membrane of the present invention (Examples 1-4 and comparative examples). Test Objective: To evaluate the disintegration performance of the membrane and verify the contribution of the bilayer microporous structure to rapid disintegration. Test Principle: The membrane disintegrates in a simulated saliva medium through saliva permeation, membrane swelling, and structural collapse. The disintegration time reflects the immediate-release performance. Experimental Method: Refer to the disintegration time limit test method in General Chapter 0921 of the 2020 edition of the Chinese Pharmacopoeia, Part IV. A single membrane tablet was placed in a basket, and 900 mL of artificial saliva (pH 6.8, 37±0.5℃) was added. The rotation speed was 100 rpm, and the time required for complete membrane disintegration (no residual particles and able to pass through a sieve) was recorded. Six tablets were tested in parallel, and the mean ± standard deviation (n=6) was taken. Standard Basis: General Chapter 0921 of the 2020 edition of the Chinese Pharmacopoeia, Part IV. Key Parameters: Medium volume 900 mL, temperature 37±0.5℃, rotation speed 100 rpm, artificial saliva pH 6.8. Data processing: Calculate the average disintegration time, with a pass / fail standard of ≤45 seconds.

[0247] Experiment 2 Mechanical Performance Testing

[0248] Test Subject: Sublingual immediate-release therapeutic membrane of this invention. Test Objective: To evaluate the mechanical strength and flexibility of the membrane, and to verify the contribution of the dense base layer in the bilayer structure to resist brittleness. Test Principle: The stress-strain relationship of the membrane material under tensile force reflects its mechanical integrity; tensile strength characterizes tensile properties, and elongation at break characterizes flexibility. Experimental Method: A texture analyzer (TA.XTplus) equipped with a membrane tensile fixture was used. The membrane was cut into 10mm × 50mm strips (n=5), with a clamping distance of 30mm, and stretched at a rate of 1mm / s until fracture. The maximum tensile force (F) and elongation at break (ε) were recorded. Tensile strength (σ) was calculated as σ = F / (membrane width × membrane thickness). Standard Basis: Refer to ASTM D882-18 standard for testing the tensile properties of thin films. Key Parameters: Sample size 10mm × 50mm, clamping distance 30mm, stretching rate 1mm / s, test temperature 25℃, relative humidity 50%. Data processing: Calculate the average tensile strength (MPa) and average elongation at break (%), and give the mean ± standard deviation.

[0249] Experiment 3 Moisture Determination

[0250] Test Subject: Sublingual immediate-release therapeutic membrane of this invention. Test Objective: To determine the free water content within the membrane and verify the effectiveness of the low dew point drying process in controlling moisture content to ≤2.0 wt%. Test Principle: The Karl Fischer method is based on the chemical reaction of iodine oxidizing sulfite to quantitatively determine moisture content. In the reaction, 1 mol of water consumes 1 mol of iodine, and the water content is calculated by coulometric titration. Experimental Method: A Karl Fischer moisture analyzer (automatic coulometric method) was used. Approximately 50 mg of the membrane sample was accurately weighed and placed in the reaction cell. Anhydrous methanol was used as the solvent. Iodine was generated by electrolysis and reacted with the water in the sample. The instrument automatically recorded the endpoint and calculated the moisture content. Three parallel determinations were performed, and the mean ± standard deviation (n=3) was taken. Standard Basis: Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0832, Moisture Determination Method (Kal Fischer Method). Key Parameters: Sample amount approximately 50 mg, solvent anhydrous methanol, electrolysis current 50-200 mA, endpoint drift <5 μg / min. Data processing: Moisture content (wt%) = (water equivalent consumed in titration / sample mass) × 100%, the pass standard is ≤2.0wt%.

[0251] Experiment 4 In vitro dissolution test

[0252] Test Subject: Sublingual immediate-release therapeutic film of this invention. Test Objective: To evaluate the in vitro dissolution behavior of misoprostol and verify the promoting effect of rapid wetting of nanodomains on immediate-release performance. Test Principle: In simulated saliva medium, the drug disintegrates and diffuses into the dissolution medium. The dissolution rate and cumulative dissolution amount reflect the drug release characteristics. Experimental Method: The paddle method (Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0931, Dissolution Determination Method II) was used. A single film tablet was placed in 900 mL of artificial saliva (pH 6.8, containing 0.5% Tween 80 for solubilization, 37±0.5℃). The paddle was rotated at 50 rpm, and 5 mL samples were taken at 1, 2, 3, 5, 10, 15, and 30 minutes (with an equal volume of fresh medium added). After filtration through a 0.45 μm filter membrane, the misoprostol concentration was determined by HPLC, and the cumulative dissolution percentage was calculated. Six tablets were tested in parallel. Standard Basis: Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0931. Key parameters: Medium: 900 mL artificial saliva, pH 6.8; Temperature: 37 ± 0.5℃; Rotation speed: 50 rpm; Sampling time points: 1 / 2 / 3 / 5 / 10 / 15 / 30 min. Data processing: Plot dissolution curves (time vs. cumulative dissolution %), calculate the dissolution amount (Q15) after 15 minutes, and the pass / fail standard is Q15 ≥ 80%.

[0253] Experiment 5: Measurement of nanometer-scale particle size and zeta potential

[0254] Test Object: Cyclodextrin nanodomains in the film-forming solution of this invention. Test Objective: To determine the median diameter and surface potential of the nanodomains' volume distribution, verifying the effectiveness of high-shear dispersion in forming stable nanodomains (80-200 nm, zeta potential ≥ 15 mV). Test Principle: Dynamic light scattering (DLS) calculates particle size distribution through the intensity fluctuations of scattered light from the Brownian motion of particles; electrophoretic light scattering (ELS) calculates the zeta potential through the migration velocity of particles in an electric field. Experimental Method: A Zetasizer NanoZS dynamic light scattering instrument was used. The film-forming solution was diluted 100 times with anhydrous ethanol, and 1 mL was placed in a cuvette. The particle size distribution (median diameter D50) and zeta potential were measured at 25°C. The measurement angle was 173° (backscattering), and the measurement was automatically performed after equilibration for 2 minutes. Each sample was measured three times. Standard Basis: Refer to ISO 22412:2017 Particle size analysis—Dynamic light scattering method and ISO 13099:2012 Determination of colloid electrophoretic mobility. Key parameters: dilution factor 100-fold, measurement temperature 25℃, measurement angle 173°, refractive index 1.330, viscosity 0.89 mPa·s (ethanol-water mixed solvent). Data processing: median diameter D50 (nm) ± standard deviation and zeta potential (mV) ± standard deviation of volume distribution are given, n=3.

[0255] Experiment 6: Determination of Content Uniformity

[0256] Test Subject: Single tablet of the sublingual immediate-release therapeutic film of this invention. Test Objective: To evaluate the uniformity of misoprostol content among single tablets and verify process stability and batch consistency. Test Principle: The content of misoprostol in a single tablet was quantitatively determined by HPLC, and uniformity was evaluated by the relative standard deviation (RSD) of 10 tablets. Experimental Method: Ten tablets were randomly selected and placed individually in a 25 mL volumetric flask. Methanol-water (70:30) was added and sonicated for 10 minutes. After adjusting the volume, the solution was filtered through a 0.45 μm filter membrane. HPLC Conditions: C18 column (250 mm × 4.6 mm, 5 μm), mobile phase methanol-0.05 mol / L potassium dihydrogen phosphate buffer (pH 3.5) = 70:30, flow rate 1.0 mL / min, detection wavelength 200 nm, column temperature 30 °C, injection volume 20 μL. External standard method was used for quantification. Standard Basis: Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0941, Content Uniformity Test Method, and General Chapter 0512, High Performance Liquid Chromatography. Key Parameters: Sample size: 10 tablets; Solvent: Methanol-Water 70:30; Column: C18; Mobile phase ratio: 70:30; Flow rate: 1.0 mL / min; Wavelength: 200 nm. Data Processing: Calculate the content (μg / tablet) and percentage of labeled amount per tablet; calculate the mean, standard deviation, and RSD; the pass standard is RSD ≤ 15% and labeled amount per tablet is 85.0-115.0%.

[0257] Experiment 7 Accelerated Stability Test

[0258] Test Subject: Sublingual immediate-release therapeutic film (aluminum-aluminum blister packaging) of the present invention. Test Objective: To evaluate the stability of the film under accelerated conditions and verify the role of low water content control in ensuring chemical stability. Test Principle: Under accelerated conditions (high temperature and high humidity), the rates of drug degradation, moisture change, and performance change are accelerated. The shelf life is predicted by examining indicators such as appearance, content, moisture, and disintegration time. Experimental Method: The packaged film was placed in a stability test chamber under accelerated conditions of 40±2℃ / relative humidity 75±5% for 0, 1, 2, 3, and 6 months. Samples were taken at each time point for testing: appearance (visual inspection for discoloration and damage), misoprostol content (HPLC method, same as Experiment 6), moisture (Karl Fischer method, same as Experiment 3), and disintegration time (same as Experiment 1). Three batches of samples were tested at each time point. Standard Basis: ICH Q1A(R2) Stability Testing Guidelines and Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 9001, Stability Testing Guidelines for Active Pharmaceutical Ingredients and Pharmaceutical Preparations. Key parameters: Temperature 40±2℃, relative humidity 75±5%, observation period 0 / 1 / 2 / 3 / 6 months, test indicators: appearance / content / moisture / disintegration time. Data processing: Data at each time point are listed, content-time curves are plotted, degradation trends are analyzed, and the 6-month stability is evaluated to ensure it meets the requirements (content ≥90%, moisture ≤2.5wt%, disintegration time ≤50s).

[0259] The above Figure 5 – Figure 10 Together, they demonstrate that the composition and surface chemistry of the sublingual immediate-release therapeutic film of Example 1 of the present invention are consistent and mutually corroborative: Figure 5 The XPS survey spectrum showed that C and O were the main elements, accompanied by characteristic peaks of N, Cl and Na, which is consistent with the formulation characteristics of hydroxypropyl methylcellulose, polyvinylpyrrolidone and 2-hydroxypropyl-β-cyclodextrin as the main components, and containing excipients and trace amounts of inorganic ions. Figure 6 The high-resolution C 1s spectrum showed components such as 284.8 eV (C–C / C–H), 286.3 eV (C–O / C–N), and 288.0–288.5 eV (O–C=O / ester or carboxyl group), confirming the presence of polysaccharide / polymer and organic acid buffer system. Figure 7 The 1s spectrum of O can be decomposed into peaks at 531.5 eV (C=O / carbonyl) and 532.8 eV (C–O / alcohol ether), further supporting the chemical environment dominated by oxygen-containing functional groups such as HPMC, PVP and cyclodextrin. Figure 8 The peak of N 1s at 399.5–400.5 eV corresponds to the possible complexed nitrogen in the PVP pyrrolidone amide nitrogen and sweetener / buffer system, proving that nitrogen-containing polymers participate in the surface composition; Figure 9 The Cl 2p peaks at 198–200 eV (Cl 2p3 / 2 / 2p1 / 2 double peaks) are consistent with the trace chlorine sources introduced from the misoprostol raw material and processing, and the peaks are symmetrical with a reasonable signal-to-noise ratio, thus eliminating instrument artifacts. Figure 10 The singlet of Na 1s at 1071–1072 eV corresponds to Na+ provided by sodium citrate, and its relative atomic content matches the semi-quantitative results of the survey spectrum. The binding energy positions, peak shapes, and area ratios of each high-resolution spectrum are consistent with the reference values ​​in the literature and databases, and the element types, valence states, and formulation sources correspond one-to-one. Therefore, the conclusions of the above figures are consistent and reproducible, fully demonstrating the correctness of the XPS characterization.

[0260] Under fixed conditions (misoprostol loading 0.8 wt%, polyvinylpyrrolidone K30 to misoprostol mass ratio 15:1, plasticizer glycerol to sorbitol mass ratio 2:2 and total plasticizer to misoprostol mass ratio 8:1, sucralose 0.10 wt%, citric acid 0.20 wt%, sodium citrate 0.20 wt%, wet film thickness 150 μm, high shear dispersion at 10000 rpm for 6 minutes, two-stage drying process at 30℃ for 10 minutes followed by at 25℃ for 12 minutes, drying environment dew point -12℃), a systematic single-factor experiment was conducted to comprehensively investigate the influence of four key parameters—hydroxypropyl methylcellulose ratio, cyclodextrin ratio, total film thickness, and ethanol volume fraction—on the film performance, fully demonstrating the scientific nature of the technical solution design and the rationality of the parameter range selection in this invention. Figure 1The study revealed that when the mass ratio of hydroxypropyl methylcellulose to misoprostol is in the range of 100-130:1, the disintegration time and tensile strength reach the optimal balance point, with the disintegration time stabilizing at 33-36 seconds and the tensile strength reaching 8.5-11.2 MPa. When the mass ratio is 70:1 and 75:1, the membrane strength decreases significantly to 5.8-6.2 MPa, while the disintegration time increases to 45-48 seconds and the standard deviation increases to 3.8-4.5 seconds, reflecting the deterioration of stability. When the mass ratio reaches 160:1, although the tensile strength increases to 15.2 MPa, the disintegration time increases to 52 seconds, far exceeding the quality control standard of 45 seconds, and the standard deviation reaches 5.2 seconds. This indicates that the 80-150:1 range is scientifically determined based on the performance boundary, ensuring that the membrane has sufficient mechanical integrity and meets the requirements for rapid release. The 100:1 ratio selected in Example 1 is in the middle of the optimal range (115:1 is the shortest disintegration time of 33.2 seconds), which has sufficient process robustness and performance reserves. Figure 2 It was confirmed that when the mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol was in the range of 20-35:1, the dissolution rate reached an excellent level of 92-96% within 15 minutes, and the median diameter of the nanodomains was controlled at 88-120 nm. When the cyclodextrin ratio was 8:1, the nanodomain particle size increased dramatically to 220 nm with a standard deviation of 18 nm, resulting in insufficient inclusion efficiency and causing the dissolution rate to drop sharply to 72.5%. When the ratio was increased to 45:1, although the nanodomains were further reduced to 82 nm, the marginal effect of the dissolution rate improvement decreased to only 94.8%, which was not significantly different from the 96.0% of 40:1 and significantly increased the raw material cost. The 20:1 ratio used in Example 1 ensured a high dissolution rate (92%) while taking into account economy and was at the beginning of the rapid performance improvement range. This range was designed to fully consider the balance between the inclusion saturation of cyclodextrin molecules on misoprostol and the formation kinetics of nanodomains. Figure 3 The study revealed that when the total membrane thickness was in the range of 25-42 μm, the disintegration time remained at 33-38 seconds and the tensile strength reached 6.5-10.2 MPa, achieving a synergistic optimization of rapid disintegration and mechanical strength. When the membrane thickness was 15 μm, the tensile strength was only 3.2 MPa, making the membrane prone to breakage and increasing the standard deviation to 0.6 MPa, reflecting a decrease in quality stability. When the membrane thickness reached 70 μm, the disintegration time was extended to 58 seconds, which seriously deviated from the rapid release requirement, and the standard deviation reached 5.5 seconds, indicating uneven wetting inside the membrane. Example 1 selected a membrane thickness of 35 μm, which ensured sufficient strength of 8.5 MPa and maintained rapid disintegration for 35 seconds, placing it in the middle region of performance balance (30-35 μm is the optimal range for comprehensive performance). The determination of this parameter window was based on the quantitative correlation between salivary osmotic kinetics and polymer network strength. Figure 4The results show that when the ethanol volume fraction is in the range of 60-80 vol%, the median diameter of the nanodomain is stable at 112-120 nm and the free water content is controlled at 1.0-1.5 wt%, which meets the quality standard of ≤2.0 wt%. When the ethanol content is 30 vol%, the polymer solubility is insufficient, resulting in large nanodomains (150 nm). The slow evaporation of the solvent causes the free water to reach 2.3 wt%, which accelerates the hydrolysis and degradation of misoprostol. When the ethanol content reaches 95 vol%, although the nanodomain shrinks to 105 nm, the free water drops to 0.6 wt%, which may lead to increased membrane brittleness and affect flexibility. The rapid evaporation of ethanol also affects the uniformity of film formation. Example 1 uses 60 vol% ethanol to balance the dual requirements of phase separation induction efficiency and moderate water retention, which is at the beginning of the range where the free water content decreases rapidly.The comprehensive data from four single-factor experiments fully demonstrate that the parameter ranges of this invention are determined based on the scientific boundaries of performance indicators rather than being arbitrarily set. Each parameter exhibits continuity and regularity in performance variation within its range, with obvious inflection points or deterioration trends appearing at the range boundaries (e.g., at a hydroxypropyl methylcellulose ratio of 80:1, the disintegration time is 42 seconds, close to the 45-second standard; at 150:1, the disintegration time begins to significantly increase from 40.5 seconds; at a cyclodextrin ratio of 10:1, the dissolution rate is 78.2%, significantly lower than 85%; at 40:1, the dissolution rate is 96.0%, close to saturation; at a film thickness of 20 μm, the tensile strength is 5.2 MPa, close to the minimum requirement; at 60 μm, the disintegration time reaches the upper limit of control at 45 seconds; at 40 vol% ethanol, the free water content is 1.9 wt%, close to the 2.0 wt% standard; at 90 vol%, the free water content is 0.8 wt%, starting to be too low). The parameter combination in Example 1 (hydroxypropyl methylcellulose ratio 100:1, cyclodextrin ratio 20:1, total film thickness 35...) The excellent comprehensive performance (disintegration time 35 seconds, tensile strength 8.5 MPa, 15-minute dissolution rate 92%, median nanoscale diameter 120 nm, free water 1.5 wt%) is achieved because the nanoscale size and ethanol content (60 vol%) are all within or near the optimal range of each single factor. This fully verifies the inherent logic and parameter synergy of the technical solution design. It confirms that the present invention regulates the constraint relationship between membrane mechanical properties and disintegration rate by precisely controlling the hydroxypropyl methylcellulose ratio, constructs an efficient nano-inclusion system to enhance drug dissolution kinetics by optimizing the cyclodextrin ratio, balances the contradiction between mechanical strength and disintegration rate requirements by membrane thickness design, and controls the dual indicators of nanoscale size and water residue by adjusting the phase separation process through ethanol content. The invention also utilizes a unified excipient system (polyvinylpyrrolidone K30 as film-forming aid 15:1, mixed plasticizer glycerol and sorbitol 2:2 total ratio 8:1, pH buffer system citric acid / sodium citrate 0.20 wt%, sucralose flavoring agent 0.10 wt%). With a standardized process platform (wet film thickness of 150 μm, high shear dispersion at 10,000 rpm for 6 minutes to ensure uniform dispersion, two-stage drying at 30℃ for 10 minutes for rapid curing followed by slow drying at 25℃ for 12 minutes, and strict control of ambient humidity at a dew point of -12℃), a fast-dissolving oral film with rapid release (disintegration time of 28-42 seconds, dissolution rate of 88-95% in 15 minutes), stability (free water 1.0-1.9 wt%, content retention rate of 95.8-97.2% in 6 months), uniformity (content uniformity RSD of 2.5-3.5%), and excellent mechanical properties (tensile strength of 5.2-12.2 MPa) was achieved. The determination of the range of each key parameter is based on sufficient experimental evidence and theoretical support, and the overall technical solution presents a high degree of rationality, reliability, and effectiveness.

[0261] Figure 5 – Figure 10Together, they demonstrate that the composition and surface chemistry of the sublingual immediate-release therapeutic film of Example 1 of the present invention are consistent and mutually corroborative: Figure 5 The XPS survey spectrum showed that C and O were the main elements, accompanied by characteristic peaks of N, Cl and Na, which is consistent with the formulation characteristics of hydroxypropyl methylcellulose, polyvinylpyrrolidone and 2-hydroxypropyl-β-cyclodextrin as the main components, and containing excipients and trace amounts of inorganic ions. Figure 6 The high-resolution C 1s spectrum showed components such as 284.8 eV (C–C / C–H), 286.3 eV (C–O / C–N), and 288.0–288.5 eV (O–C=O / ester or carboxyl group), confirming the presence of polysaccharide / polymer and organic acid buffer system. Figure 7 The 1s spectrum of O can be decomposed into peaks such as 531.5 eV (C=O / carbonyl) and 532.8 eV (C–O / alcohol ether), which further supports the chemical environment dominated by oxygen-containing functional groups such as HPMC, PVP and cyclodextrin. Figure 8 The peak of N 1s at 399.5–400.5 eV corresponds to the possible complexed nitrogen in the PVP pyrrolidone amide nitrogen and sweetener / buffer system, proving that nitrogen-containing polymers participate in the surface composition; Figure 9 The Cl 2p peaks at 198–200 eV (Cl 2p3 / 2 / 2p1 / 2 double peaks) are consistent with the trace chlorine sources introduced from the misoprostol raw material and processing, and the peaks are symmetrical with a reasonable signal-to-noise ratio, thus eliminating instrument artifacts. Figure 10 The singlet of Na 1s at 1071–1072 eV corresponds to Na+ provided by sodium citrate, and its relative atomic content matches the semi-quantitative results of the survey spectrum. The binding energy positions, peak shapes, and area ratios of each high-resolution spectrum are consistent with the reference values ​​in the literature and databases, and the element types, valence states, and formulation sources correspond one-to-one. Therefore, the conclusions of the above figures are consistent and reproducible, fully demonstrating the correctness of the XPS characterization.

[0262] Scanning electron microscopy characterization fully confirms the successful implementation of the bilayer structure design and the precise controllability of its microstructure features in this invention. Figure 11 The surface cross-sectional morphology diagram clearly reveals that in Example 1, the phase separation process induced by 60 vol% ethanol induced a through-hole microporous network structure in the surface region. Cross-sectional observation shows that the channels exhibit a vertically oriented interconnected feature along the thickness direction. Figure 12The top-view morphology of the surface layer further verifies the uniform distribution characteristics of the microporous structure from a surface perspective. The top-view image shows that the surface layer has uniformly dispersed elliptical or irregular micropore openings, which fully verifies the scientific nature of the technical solution design of the present invention and the representativeness of the parameter selection in Example 1. It provides direct microstructural evidence for the simultaneous solution of three essential pain points of sublingual fast-dissolving film for the treatment of postpartum hemorrhage: the coupling contradiction between microporous fast-release structure and anti-fragility transportability, the conflict between low water content and high stability and oral rapid wetting and dissolution water activity, and the conflict between batch-to-batch thickness mechanical uniformity and the high loading fast-release requirement of cyclodextrin nanodomain formation.

[0263] The performance of the examples and comparative examples is summarized in Table 1. The performance differences between the comparative examples and the examples mainly stem from multi-dimensional performance degradation caused by deviations in key process parameters or formulation composition: Comparative Example 1 suffered from insufficient film-forming properties due to the hydroxypropyl methylcellulose ratio decreasing to 70:1, which is below the lower limit of the claims. The disintegration time was prolonged to 48 seconds and the tensile strength was only 5.8 MPa. At the same time, the loose film structure caused the dissolution rate to decrease to 75% after 15 minutes, the content uniformity RSD increased to 4.8%, and the long-term stability also decreased to 93.2% due to insufficient film density. Comparative Example 2 suffered from excessively high hydroxypropyl methylcellulose ratio of 160:1, which resulted in excessively high viscosity of the film-forming liquid. Although the tensile strength increased to 10.8 MPa, the disintegration time was significantly prolonged to 52 seconds. The excessively thick polymer network severely hindered drug release, resulting in a dissolution rate of only 68%. The elongation at break decreased to 25% due to increased rigidity. Comparative Example 3 suffered from insufficient nanodomain formation (median diameter increased to 220 nm) and an absolute value of only 8 zeta potential due to the cyclodextrin ratio decreasing to 8:1, which is below the lower limit. The mV indicates poor stability; low inclusion efficiency reduced the dissolution rate to 72%, and insufficient cyclodextrin as a hydrophilic component led to excessive free water exceeding the limit to 2.2 wt%. In accelerated stability testing, excessive water triggered misoprostol hydrolysis, reducing the 6-month retention rate to 91.8%. Comparative Example 4, with an excessively high cyclodextrin ratio of 45:1, although achieving a nanoscale domain of 185 nm (still near the upper limit), significantly increased costs. While the dissolution rate improved to 85%, approaching the level of the example, it was economically unsustainable. Excessive cyclodextrin occupied formulation space, compressing the proportions of other components and affecting overall balance. Comparative Example 5, with a polyvinylpyrrolidone (PVP) K30 ratio reduced to 8:1 (below the lower limit), resulted in insufficient film-forming assistance. Insufficient cross-linking of polymer segments during film formation reduced the tensile strength to 6.5 MPa and the elongation at break to only 35%. Simultaneously, insufficient PVP as a hydrophilic carrier affected drug dispersion uniformity, causing free water to rise to 2.1 wt%. The content uniformity RSD of the excess wt% of the sample was 4.5%. Comparative Example 6 suffered from a severe lack of membrane flexibility due to a plasticizer ratio of 3:1, below the lower limit. Although the tensile strength remained at 5.5 MPa, the elongation at break plummeted to 28%, indicating increased membrane brittleness and susceptibility to breakage. Insufficient plasticizer reduced the free volume between polymer segments, affecting drug diffusion. Although the disintegration time was controlled at 36 seconds, the membrane exhibited poor resistance to brittleness during storage and transportation. Comparative Example 7 suffered from a severe lack of mechanical integrity due to a total membrane thickness of 15 μm, below the lower limit. The tensile strength was only 3.2 MPa, and the elongation at break was 22%, making the membrane extremely prone to breakage. Although the ultrathin membrane disintegrated rapidly (30 seconds), the content uniformity RSD soared to 6.8%, indicating uneven drug distribution. The inability to effectively form a bilayer structure affected functional stratification. Comparative Example 8 suffered from a total membrane thickness of 70 μm, exceeding the upper limit, resulting in a significantly prolonged disintegration time of 58 seconds, exceeding the 45-second standard. Although the tensile strength of the excessively thick membrane increased to 15, the overall disintegration time was significantly prolonged to 58 seconds, exceeding the 45-second standard.The film has a tensile strength of 5 MPa and an elongation at break of 52%, but it severely hinders saliva penetration. The drug diffusion path is prolonged, resulting in a dissolution rate of only 65% ​​after 15 minutes, far below the 80% standard. The thick film design violates the requirements for immediate release. Comparative Example 9, due to its single-layer structure instead of a double-layer design, cannot form functional partitions between a microporous surface layer and a dense base layer. The lack of a microporous structure prolongs the disintegration time to 50 seconds. The single-layer homogeneous structure cannot induce the formation of nanodomains through phase separation (labeled "no nanodomains"), resulting in an absolute value of only 5 mV for the zeta potential, indicating the absence of a stable nano-dispersion system. The low drug inclusion efficiency reduces the dissolution rate to 70%. Although the single-layer film has acceptable mechanical properties (tensile strength 9.2 MPa), its immediate release function is severely impaired. Comparative Example 10, due to the increase in the first-stage drying temperature to 45°C, which is higher than the 30°C of the example, leads to accelerated thermal degradation of misoprostol. Although the free water is well controlled (1.2 MPa), the thermal degradation is still significant. (wt%) However, high temperature damaged the drug's stability, causing the 6-month content retention rate to plummet to 88.5%, far lower than the 95.8-97.2% of the examples. High-temperature drying also affected the quality of nanodomain formation, causing the median diameter to drop to 95 nm, close to the lower limit, but no significant improvement was observed in zeta potential and dissolution performance. Comparative Example 11, due to the omission of the high-shear dispersion step and the use of only ordinary magnetic stirring, resulted in a severe deficiency in the formation of cyclodextrin nanodomains. The median diameter of the nanodomains surged to 280 nm, far exceeding the upper limit of 200 nm, and the absolute value of the zeta potential was only 6 mV, indicating that the dispersion system was extremely unstable. The low inclusion efficiency of the large-particle nanodomains reduced the dissolution rate to 78%. Insufficient shear also led to uneven dispersion of the film-forming liquid components, causing the content uniformity RSD to rise to 6.5%. The wide distribution of nanodomain particle size (standard deviation ±25 nm) reflected poor dispersion system quality. Comparative Example 12, due to the reduction of the ethanol volume fraction to 30%, resulted in a significant deficiency in the formation of cyclodextrin nanodomains. The vol% was below the lower limit, resulting in insufficient solubility of hydroxypropyl methylcellulose and cyclodextrin. Low alcohol content led to insufficient polymer swelling, affecting the uniformity of the film-forming solution. Weakened phase separation induction resulted in a median nanodomain diameter of 150 nm with uneven distribution. Slow solvent evaporation caused drug migration during drying, leading to free water exceeding the limit to 2.3 wt%. Excessive moisture accelerated misoprostol hydrolysis, reducing the 6-month retention rate to 92.0%, and the dissolution rate decreased to 72% due to poor nanodomain quality. In Comparative Example 13, the ethanol volume fraction increased to 95 vol%, exceeding the upper limit, resulting in excessively low polarity of the film-forming solution, affecting the dissolution of hydrophilic components. High alcohol content reduced cyclodextrin solubility, affecting nanodomain formation (the median diameter of 105 nm, although within the range, indicated a high ionic strength environment due to a zeta potential of -19 mV). Rapid solvent evaporation resulted in excessively low free water (0.8 wt%). The presence of wt% alcohol reduced membrane flexibility (30% elongation at break), and the high alcohol residue may have accelerated misoprostol degradation, causing the 6-month retention rate to drop to 90.2%. Although the dissolution rate was still acceptable (85%), both stability and flexibility were compromised.

[0264] Table 1 Summary of performance of examples and comparative examples

[0265]

[0266] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A postpartum hemorrhage treatment composition, characterized by, It is a sublingual immediate-release therapeutic film, comprising misoprostol; hydroxypropyl methylcellulose; 2-hydroxypropyl-β-cyclodextrin; polyvinylpyrrolidone K30; and a plasticizer selected from glycerin and / or sorbitol; and has the following characteristics: a) The mass ratio of hydroxypropyl methylcellulose to misoprostol is 80-150:1; b) The mass ratio of 2-hydroxypropyl-β-cyclodextrin to misoprostol is 10-40:1; c) The mass ratio of polyvinylpyrrolidone K30 to misoprostol is 10-25:1; d) The mass ratio of plasticizer to misoprostol is 5-15:1; e) The total film thickness is 20-60 μm; f) It adopts a double-layer structure, in which the surface layer is a microporous or microfiber structure with a pore size of 0.5-5 μm, and the base layer is a dense load-bearing layer; g) The free water content within the membrane is not greater than 2.0 wt%; h) The membrane contains nanodomains with a midpoint diameter of 80-200 nm formed by the volume distribution of cyclodextrin; The disintegration time of the composition is not greater than 45 s; the absolute value of the zeta potential of the nanodomain is not less than 15 mV.

2. The composition according to claim 1, characterized in that, The thickness of the surface layer is 5-30 μm.

3. The composition according to claim 1, characterized in that, The loading of misoprostol in the membrane is 0.3-1.8 wt%.

4. The composition according to claim 1, characterized in that, The average molar degree of substitution of the 2-hydroxypropyl-β-cyclodextrin is 0.4-0.

8.

5. A method for preparing a postpartum hemorrhage treatment composition, used to prepare the composition according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Hydroxypropyl methylcellulose, 2-hydroxypropyl-β-cyclodextrin and polyvinylpyrrolidone K30 are dispersed and dissolved in a mixed solvent of water and ethanol, with an ethanol volume fraction of 40-90 vol%. After shearing and dispersing at 8000-12000 rpm for 5-8 min, misoprostol and plasticizer are added and degassing is performed. S2. Apply the film with a wet film thickness of 120-200 μm by blade coating, and dry it according to a two-stage drying curve of 30 ℃ for 8-12 min followed by 25 ℃ for 10-15 min until the free water content in the film is no more than 2.0 wt%. S3. Cut into single sheets to obtain sublingual immediate-release therapeutic films with a total film thickness of 20-60 μm, and complete the sealing and packaging.

6. The method according to claim 5, characterized in that, The degassing was carried out under a vacuum of -0.09 to -0.095 MPa for 10-20 min.

7. The method according to claim 5, characterized in that, The dew point of the dry environment of S2 is not higher than -10 ℃.

8. The method according to claim 5, characterized in that, The pore size of the surface layer is obtained through phase separation induction, and the pore size is 0.5-5 μm.

9. Use of the composition according to any one of claims 1-4 in the preparation of a medicament for treating postpartum hemorrhage, characterized in that, The composition is administered sublingually to achieve an onset time of no more than 10 minutes.

Citation Information

Patent Citations

  • Oral instant film and preparation method thereof

    CN115252587A

  • Sublingual films

    CN103476372A

  • Rasagiline or medicinal salt sublingual film agent thereof as well as preparation method and application thereof

    CN114469902A

  • Felodipine sustained release tablet and preparation method thereof

    CN120346173A